Has Promotion of Community-based Tourism been A Successful Rural Development Strategy in Northeast Thailand? - Choenkwan, Sukanlaya; Rambo, A. Terry (Forest and Society, 2025)
Promotion of community-based homestay tourism (CBT) in rural villages is an important element of Thailand’s rural development strategy. This paper assesses how the concept of community-based tourism has worked in practice by examining the present status of all 53 government-recognized homestay communities in Northeast Thailand. It also identifies the challenges faced by these communities in implementing CBT. Semi-structured interviews were conducted in every community with a total of 81 key informants. It was found that nearly half (45.3%) of these homestay communities were completely inactive because they had received no visits by tourists. The active homestay communities were classified into four types based on how they are organized, the volume of tourists received, and how benefits of tourism are shared within the communities. Only a handful of active homestay communities (5.7%) are categorized as practicing community-based tourism. This low success rate reflects the many challenges that communities seeking to implement the CBT strategy must overcome. It is concluded that if widespread development of community-based homestay tourism villages is the sole measure of success of this rural development effort, then it must be judged to have been a failure. However, if the measure of success is broadened to include increasing the economic welfare of some villagers, even if not the whole community, then the program as implemented in Northeast Thailand can be judged to have achieved somewhat greater, but still very limited success.